Empowering Science Teachers through STEM-Based Teaching Module Development Training - Permana, Handjoko; Bakri, Fauzi; Muliyati, Dewi; Mutoharoh, Mutoharoh; Primasari, Nandia; Sabrina, Putri Marsha (MJI Publisher by PT Mitra Jurnal Indonesia, 2025)
This article discusses a capacity-building initiative designed to empower science educators through a systematic training program that emphasises the development of STEM-oriented teaching modules. The program emphasised the integration of Science, Technology, Engineering, and Mathematics (STEM) into lesson plans to enhance students' problem-solving, creativity, collaboration, and critical thinking abilities. The module's primary components included problem conceptualisation, inquiry planning, experiment execution or engineering design, data analysis, and reflection. Educators were instructed to establish learning objectives aligned with STEM principles, develop authentic assessment instruments, and employ interdisciplinary approaches in their instruction. The training outcomes indicated that educators were more proficient in designing pertinent and engaging learning experiences. This initiative illustrates the significance of equipping educators with the necessary resources to effectively instruct STEM courses in alignment with the requirements of 21st-century learners.